A Fast Calculation and Rendering Method for Infrared Characteristics of Hypersonic Vehicle. (July 2020) - Bao, Chenying; Li, Ni; Gong, Guanghong; Tian, Chao; Lu, Yuanjie
Abstract: In this paper, a fast calculation and rendering method for infrared characteristics of hypersonic vehicle is proposed, which covers the overall infrared simulation process. The key point of this method is the heterogeneous interpolation algorithm, which can map the data from dense grid to sparse grid, thus greatly reducing the volume of data and improving rendering efficiency on the premise of guaranteeing the simulation reliability. Taking the hypersonic vehicle X-43A as an example, we realize the calculation and rendering of its infrared characteristics. Experimental results show that the infrared radiation characteristics of hypersonic vehicle are primely reproduced in the rendering process.